The first European a history of Alexander in the Age of Empire - Briant, Pierre 1940- (Harvard University Press, 2017)
In The First European: A History of Alexander in the Age of Empire, Pierre Briant examines the revival and rewriting of the history of Alexander the Great in 18th-century Europe. To Enlightenment thinkers Alexander exemplified the West and Europe, especially in his role as the conqueror of Asia. Classical texts, ancient history, and the new science of archaeology were all deployed in the service of European empire-building. Alexander was of interest to a variety of scholars from different parts of Europe - moralists, philosophers, economists, geographers, historians, and cartographers. In the course of the long 18th century, an entirely new image of the Macedonian conqueror emerged, as the precedent of European political and commercial expansion overseas....